All That Glitters: Devaluing the Gold Standard in the Utopias of Thomas More, Francis Bacon, and Margaret Cavendish - Martin, Catherine Gimelli (Renaissance and Reformation / Renaissance et Réforme, 2018)
Francis Bacon’s and Margaret Cavendish’s ideal societies unexpectedly follow Thomas More’s Utopia in eliminating the exchange value of gold and replacing it with a knowledge economy. Bacon’s New Atlantis (1627) and Cavendish’s Blazing World (1666) similarly pursue new “light” and shun selfish profit, private trade, capital accumulation, and conspicuous consumption. Unlike More, they allow gold to retain its traditional decorative and symbolic functions, but its “use value” completely trumps its exchange value. Cavendish uses gold to construct and glorify her Blazing World and to forge astonishing defensive weapons, but it cannot be bought, sold, or even earned since it remains exclusively imperial. Bacon restricts gold to buying new “light” or knowledge and honouring thriving families with symbolic golden grape clusters, but like the Fathers of Salomon’s House, all three societies value only beneficial knowledge and the collaborative virtues taught by their new or improved religions to further universal peace and brotherhood.